2019
DOI: 10.1007/s00348-019-2798-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic interaction of bubbles rising side-by-side in viscous liquids

Abstract: Detailed experiments are conducted to study hydrodynamic effects of two simultaneously released bubbles rising in viscous liquids. Different types of interactions are observed as a function of the liquid viscosities, leading to different bubble shapes, ranging from rigid spheres and spheroids to deformable spheroids. Bubble velocities are obtained by an automated smooth spline technique, which allows for an accurate calculation of the lift and drag forces. The results obtained for spherical bubbles are in agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…(2009), Kong et al. (2019), it is also found that such double-threaded vortices are generated during the approach of two bubbles by increasing their size.
Figure 3.Three-dimensional velocity streamlines past the left bubble within one pair at mm in the reference frame of the bubble; the contour maps describe the iso-values of the streamwise velocity field.
…”
Section: Bubble Interactions Without Applying Mfmentioning
confidence: 93%
See 1 more Smart Citation
“…(2009), Kong et al. (2019), it is also found that such double-threaded vortices are generated during the approach of two bubbles by increasing their size.
Figure 3.Three-dimensional velocity streamlines past the left bubble within one pair at mm in the reference frame of the bubble; the contour maps describe the iso-values of the streamwise velocity field.
…”
Section: Bubble Interactions Without Applying Mfmentioning
confidence: 93%
“…Recent experiments conducted by Kong et al. (2019) have also addressed the importance of the bubble wakes because the path instability is triggered in the presence of another bubble.…”
Section: Introductionmentioning
confidence: 99%
“…decrease) in Re. However, according to recent experimental results of Yamaguchi and Sanada [6] and Kong et al [10], large deformable bubbles repel each other even if Re is large. We firstly classify the trajectories of a pair of bubbles.…”
Section: Trajectories Of a Pair Of Bubblesmentioning
confidence: 98%
“…2009; Kong et al. 2019), varying the liquid properties, bubble sizes and initial separation. Depending on flow conditions, the two bubbles were found to repel or attract each other.…”
Section: Introductionmentioning
confidence: 99%